2012
DOI: 10.1016/j.intimp.2012.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of microRNAs in gastric cancer and biological significance of miR-574-3p

Abstract: The discovery of microRNAs (miRNAs) provides a new and powerful tool for studying the mechanisms, diagnosis and treatments of cancer. In this study, we employed AFFX miRNA expression chips to search for miRNAs that may be aberrantly expressed in gastric cancer tissues and to investigate the potential roles that miRNAs may play in the development and progression of gastric cancer. 14 miRNAs were found to be down-regulated and 2 miRNAs up-regulated in gastric cancer tissues compared to the normal gastric tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 28 publications
7
42
0
Order By: Relevance
“…The downregulation of miR-451 was significantly associated with gastric adenocarcinomas as compared with normal gastric mucosa (Bandres et al , 2009; Ueda et al , 2010; Konishi et al , 2012). Similarly, Oh et al (2011) identified miR-486 as a significantly downregulated miRNA in primary GC tumours and GC cell lines, and similar trend was also reported by Konishi et al (2012) and Su et al (2012). Of interest, in the current study, the expression levels of miR-451 and miR-486-5p did not change in culture medium of GC cell lines as cell counts and incubation time increased.…”
Section: Discussionsupporting
confidence: 88%
“…The downregulation of miR-451 was significantly associated with gastric adenocarcinomas as compared with normal gastric mucosa (Bandres et al , 2009; Ueda et al , 2010; Konishi et al , 2012). Similarly, Oh et al (2011) identified miR-486 as a significantly downregulated miRNA in primary GC tumours and GC cell lines, and similar trend was also reported by Konishi et al (2012) and Su et al (2012). Of interest, in the current study, the expression levels of miR-451 and miR-486-5p did not change in culture medium of GC cell lines as cell counts and incubation time increased.…”
Section: Discussionsupporting
confidence: 88%
“…Case-control approach focuses on identifying prognostic markers which are differentially expressed [29, 30]. However, case-only approach interrogates the entire dataset in an unbiased manner [3133] and may thus yield higher number of prognostic markers. We observed the same in our study, where, with the case–only method, we obtained four and six piRNAs for OS and RFS, respectively as opposed to three piRNAs each for OS and RFS.…”
Section: Discussionmentioning
confidence: 99%
“…SMAD4 overexpression could rescue the promoting effects of miR-574-3p on cancer cell growth, which additionally supports the theory that miR-574-3p may be associated with SMAD4. miRNAs are critical regulators and biomarkers for numerous types of cancers (8,(21)(22)(23)(24). There are several miRNAs that have been found to be abnormal in human osteosarcoma, including miR-141, miR-429, miR-451, miR-195, miR-183 miR-199a-3p, miR-127-3p and miR-376c (3,5,10,(25)(26)(27).…”
Section: Downregulation Of Mir-574-3p Inhibited Cell Growth and Inducmentioning
confidence: 99%